Increasing the Competency of SMKN 3 Cimahi Students Through Supply Chain Management Training - Mulyana, Aam Rachmat; Abdurahman, Khairul Rizal; Nurtjahjadi, Edi; Herawati, Siti; Ludiya, Eka; Kurniawan, Asep; Sari, Rini Mulyani (CV. Astina Mandiri, 2024)
Vocational high school 3 of Cimahi has 3 business units there are culinary, designer and laundry business with the standard like a Hotel. Product Inventory is one of the problems on VHS 3 of Cimahi. The gap arises because of uncertainty of information such as demand and delivery schedule. The important aims of this issue is supply chain management is doing well coordination between a several activities and connected with all off the supply chain until the product can flow smoothly and arrived on time, from the production process until distribution, and ensure the distribution from company to distributors, then the distributors until the product arrives to customers. This society service program provides the solution to increase the student competence on VHS 3 of Cimahi where at the student are equipped with supply chain management knowledge which has benefits if applied by students in the future, it will improve good coordination.